2013
DOI: 10.1159/000346646
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success for Smoking Cessation at the Workplace: A Longitudinal Study

Abstract: Background: The effectiveness of worksite interventions to reduce smoking is debatable. Objectives: Acomprehensive smoking cessation intervention was implemented in a community of more than 17,000 employees at three different health care companies. The primary endpoint was abstinence at 24 months (self-reported and confirmed by exhaled carbon monoxide ≤6 parts per million). Predictors of long-term abstinence were analysed by multivariable regression analysis. Methods: The study was designed as an investigator-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
(41 reference statements)
4
26
1
1
Order By: Relevance
“…The coexistence of smoking and depression has been extensively investigated, mainly because depression is the psychiatric disorder most associated with tobacco use [35]. Similar to our results, the aforementioned intervention study in Basel showed that smokers with a history of depression or current use of antidepressants were less likely to quit [34]. This may be related to common genetic mechanisms behind smoking initiation, nicotine dependence and depressive disorders [36,37].…”
Section: Health-related Predictors Of Smoking Cessationsupporting
confidence: 86%
See 1 more Smart Citation
“…The coexistence of smoking and depression has been extensively investigated, mainly because depression is the psychiatric disorder most associated with tobacco use [35]. Similar to our results, the aforementioned intervention study in Basel showed that smokers with a history of depression or current use of antidepressants were less likely to quit [34]. This may be related to common genetic mechanisms behind smoking initiation, nicotine dependence and depressive disorders [36,37].…”
Section: Health-related Predictors Of Smoking Cessationsupporting
confidence: 86%
“…A negative association between smoking cessation and chronic sputum production was also found in a recent smoking cessation intervention study conducted among 887 smoking employees in the city of Basel [34]. The coexistence of smoking and depression has been extensively investigated, mainly because depression is the psychiatric disorder most associated with tobacco use [35].…”
Section: Health-related Predictors Of Smoking Cessationmentioning
confidence: 84%
“…Given the prevalence of smoking and the associated health consequences of continued smoking, it is critical to provide effective cessation interventions. Therefore, succeeding lifelong abstinence is an essential goal from the health perspective [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Smoking-related factors associated with positive cessation outcomes include lower baseline craving [1, 2], severity of nicotine dependence [3-8], and number of cigarettes smoked per day [9-14]. Demographic variables shown to be helpful include higher educational level [15-18], older age [19, 20], and being married [21]. Studies have shown mixed results regarding gender as a determinant of successful cessation [9, 12, 20-24].…”
Section: Introductionmentioning
confidence: 99%